Identification of the HMGA2::CIBAR1-DT fusion transcript in two lipomas with chromosomal rearrangements involving chromosomes 8 and 12 - Brunetti, Marta; Andersen, Kristin; Lobmaier, Ingvild; Micci, Francesca (Frontiers in Oncology, 2026)
Background/AimLipomas are benign tumors of adipocytic origin. The most frequent chromosome rearrangement in lipomas involves the high-mobility group AT-hook 2 gene (HMGA2), which maps to 12q14. We investigated two lipomas showing rearrangements of chromosomal bands 8q22 and 12q14 in their karyotypes, with the aim of identifying the gene products affected by these aberrations.Materials and MethodsThe two lipomas were selected because their karyotype showed an 8;12-rearrangement with the very same breakpoint position. The cases were investigated using RNA sequencing, reverse transcription polymerase chain reaction (RT-PCR), Sanger sequencing techniques, Fluorescence in situ hybridization (FISH), and array comparative genomic hybridization (aCGH).ResultsRNA sequencing and RT-PCR of the two lipomas showed the presence of the HMGA2::CIBAR1-DT chimera.ConclusionsThe HMGA2::CIBAR1-DT fusion, identified here for the first time, is a recurrent transcript in lipomas.